Role of Clathrin and Dynamin in Clathrin Mediated Endocytosis/Synaptic Vesicle Recycling and Implications in Neurological Diseases - Prichard, Kate L.; O'Brien, Nicholas S.; Murcia, Sari R.; Baker, Jennifer R.; McCluskey, Adam (Frontiers in Cellular Neuroscience, 2022)
Endocytosis is a process essential to the health and well-being of cell. It is required for the internalisation and sorting of ‘cargo’ – the macromolecules, proteins, receptors and lipids of cell signaling. Clathrin mediated endocytosis (CME) is one of the key processes required for cellular well-being and signaling pathway activation. CME is key role to the recycling of synaptic vesicles (synaptic vesicle recycling (SVR)) in the brain, it is pivotal to signaling across synapses enabling intracellular communication in the sensory and nervous systems. In this review we provide an overview of the general process of CME with a particular focus on two key proteins: clathrin and dynamin that have a central role to play in ensuing successful completion of CME. We examine these two proteins as they are the two endocytotic proteins for which small molecule inhibitors, often of known mechanism of action, have been identified. Inhibition of CME offers the potential to develop therapeutic interventions into conditions involving defects in CME. This review will discuss the roles and the current scope of inhibitors of clathrin and dynamin, providing an insight into how further developments could affect neurological disease treatments.